2006
DOI: 10.1021/ie060504r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Well-Defined Star Polymer from Hyperbranched Macroinitiator Based Attapulgite by Surface-Initiated Atom Transfer Radical Polymerization Technique

Abstract: To prepare the well-defined star polymer grafted attapulgite nanofibrillar clay (WSP-ATP) with hydrophilic core and hydrophobic shell and higher percentage of grafting, the postgraft polymerization of vinyl polymer from hyperbranched macroinitiator based attapulgite (HMI-ATP) via the surface-initiated atom transfer radical polymerization (SI-ATRP) technique was investigated for the first time. The HMI-ATP, with bromoacetic ester surface groups, was prepared by the bromoacetylation of the surface hydroxyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition, it is difficult to introduce linear polymer chains onto the matrix by the "grafting from" technique, using common radical initiation procedures without generating considerable amounts of wasteful non-grafted homopolymers as by-products. The emerging "controlled chain growth" technique, such as atom transfer radical polymerization (ATRP) [24,25], has been demonstrated to be applicable to the grafting of welldefined homopolymers [26,27], diblock copolymers [28][29][30][31], graft copolymers [32], star polymers [33], and hyperbranched polymers [34,35] from chloroalkylated solid surfaces, such as nanoparticles, nanotubes, nanowires, clays and polybutadiene microgels [36]. Nchlorosulfonamidated polystyrene resin as a matrix has also been reported by Bicaka and co-workers [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is difficult to introduce linear polymer chains onto the matrix by the "grafting from" technique, using common radical initiation procedures without generating considerable amounts of wasteful non-grafted homopolymers as by-products. The emerging "controlled chain growth" technique, such as atom transfer radical polymerization (ATRP) [24,25], has been demonstrated to be applicable to the grafting of welldefined homopolymers [26,27], diblock copolymers [28][29][30][31], graft copolymers [32], star polymers [33], and hyperbranched polymers [34,35] from chloroalkylated solid surfaces, such as nanoparticles, nanotubes, nanowires, clays and polybutadiene microgels [36]. Nchlorosulfonamidated polystyrene resin as a matrix has also been reported by Bicaka and co-workers [10].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the curve of PAL that the mass loss is about 7% when the temperature increases from 25 to 150 °C, which is caused by the loss of water adsorbed on the surface of PAL, and the subsequent weight loss of about 700 °C can be attributed to the loss of water of crystal in PAL. 27 The total weight loss of 17.03% is observed after calcination at 800 °C. During the calcination process of the both composites, the loss of weight is about 8% at 100 °C, which is related to the volatilization of surface adsorption water.…”
Section: Resultsmentioning
confidence: 99%
“…During polymerization, no precipitation was observed; this indicated that no homopolymerization occurred, as was expected for the SI-ATRP technique. 39 The kinetic reaction at room temperature was followed by a progressive mass increase of the films. A relative linear plot of the graft yield versus reaction time was obtained; this implied first-order kinetics of the SI-ATRP process (Fig.…”
Section: Si-atrp Of Hemamentioning
confidence: 99%